Utilization of melinjo waste for product diversification to increase family income in Cigandeng Village, Pandeglang Regency - Mohammad Ischak; Dian Octaviani; Mustamina Maulani; Rendi Amanda; Waldah Nurjamilah (Community Empowerment, 2024)
Increasing family income in rural areas heavily relies on the active role of housewives. In Cigandeng Village, Menes District, many housewives are engaged in melinjo cracker production but only receive limited daily wages. Waste from the melinjo cracker-making process, such as the shells (inner skin) and outer skin, holds significant potential to be processed into high-value food products. This Community Service Program (PkM) aims to empower housewives by increasing family income through the diversification of products based on melinjo waste. The methods employed include participatory training involving experts to develop recipes and production techniques for melinjo waste-based food products. The training outcomes demonstrated improved participant skills in producing various processed products, such as dodol, kembang goyang, lidah kucing, semprong cookies, brownies, and putri salju cookies. These products have started to be commercialized by some training participants, contributing significantly to family income. This program not only encourages product diversification but also reduces waste, creating added value for the community.